2014
DOI: 10.1134/s2070046614020046
|View full text |Cite
|
Sign up to set email alerts
|

On stochastic generation of ultrametrics in high-dimensional Euclidean spaces

Abstract: We present a proof of the theorem which states that a matrix of Euclidean distances on a set of specially distributed random points in the n-dimensional Euclidean space R n converges in probability to an ultrametric matrix as n → ∞. Values of the elements of an ultrametric distance matrix are completely determined by variances of coordinates of random points. Also we preset a probabilistic algorithm for generation of finite ultrametric structures of any topology in high-dimensional Euclidean space. Validity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…It was shown that, for a special class of laws of distributions of points in R n , the normalized matrix of Euclidean distances on the set of points converges in probability as n → ∞ to the ultrametric matrix. In the present paper, we extend the result of [11] to the case when the coordinates of random points are statistically dependent. Our main result is Theorem 3 of Section 4, which states that, under a number of conditions on the expectations of the variance and the covariance of coordinates of random points, the matrix of Euclidean distances of a random realization of a finite number of points tends in probability as n → ∞ to the ultrametric matrix.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…It was shown that, for a special class of laws of distributions of points in R n , the normalized matrix of Euclidean distances on the set of points converges in probability as n → ∞ to the ultrametric matrix. In the present paper, we extend the result of [11] to the case when the coordinates of random points are statistically dependent. Our main result is Theorem 3 of Section 4, which states that, under a number of conditions on the expectations of the variance and the covariance of coordinates of random points, the matrix of Euclidean distances of a random realization of a finite number of points tends in probability as n → ∞ to the ultrametric matrix.…”
Section: Discussionmentioning
confidence: 67%
“…It is seen that with increasing n the random realization of the matrix d (2,2,2) n (3) becomes more and more close to the ultrametric matrix. Using the results of [11] one may show that as n → ∞ the random realization of the matrix d (2,2,2) n (3) will approach in probability the ultrametric matrix of the form…”
Section: Illustrative Example I Independent Coordinatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that ultrametricity is naturally rooted in high dimensionality, randomness, and sparse statistics, has been unambiguously shown recently in Ref. [28]. It was proven that in a D-dimensional Euclidean space the distances between points in a highly sparse sampling tends to the ultrametric distances as D → ∞.…”
Section: Ultrametricitymentioning
confidence: 88%
“…The time complexity of this method is O(N 3 ), where N is the data size. Zubarev (2014) considers an index defined by taking the average of the ratio of the second largest length by the maximum length in the triangles of a data set. This also has a time-complexity of O(N 3 ).…”
Section: Introductionmentioning
confidence: 99%